Accumulative weekly load in a professional football team: with special reference to match playing time and game position - Casamichana, David; Martín-García, Andrés; Gómez Díaz, Antonio; S Bradley, Paul; Castellano, Julen (Biology of Sport, 2022)
The aim of this study was to compare weekly accumulative load during the in-season competitive period by professional soccer players according to the amount of time played in official matches (90-min, >60-min, 19.8 km·h-1), sprint meters (SPR; >25.2 km·h-1), high metabolic load distance (HMLD; >25.5 W·kg-1), number of accelerations (ACC; >3 m·s-2) and decelerations (DEC; 60-min vs. <60-min and 0-min), HSR (90-min vs. <60-min and 0-min) and SPR (90-min vs. <60-min and 0-min). In addition, less positional variation was observed in relation to the competition requirements. This information would allow coaches to refine the required load with the objective of optimizing performance to soccer players.